A Comparative Study on the Opportunities and Threats of the Internet and Considering the Rights of Kids Online in Australia, Brazil, Iran, and South Africa - Fereshteh Naseri; Davoud Taghvaei; Bahram Saleh Sedghpour; Gholam Ali Ahmadi (Comparative Education Society of Iran ( CESIR), 2021)
The present study aims to compare the opportunities and threats of the Internet and considering the rights of kids online in Australia, Brazil, Iran, and South Africa. The research method was qualitative-comparative using Bereday's approach. The strategy for selection of countries was "different systems, different‌ outputs". The population included 210 studies from which 45 samples related to research objectives were selected. Primary documents and self-assessment method   were used for increasing the validity and reliability of references, respectively. John Stuart Mill's agreement and difference method was used for data analysis and George Bereday's method was used for presenting the results. The findings indicated that most similarities are in Internet threats and most differences are in the opportunities created for kids online and considering their rights in these countries. Cyber-bullying and Internet addiction threaten all kids online in such countries. In terms of considering the rights of kids online, Australia is at the top of the list, followed by Brazil, South Africa, and Iran. No serious measure has been taken in Iran to ensure the rights of kids online due to weak infrastructure, low internet speed, and legal gap. Based on the findings, cyberspace authorities and planners in Iran are suggested to take more legal, executive, and educational measures in the framework of international cooperation to achieve the rights and welfare of kids online.